HEALTH AND HUMAN WELLNESS IN MODERN TIMES: HOSTAGE TO TECHNOLOGY AND HUMAN INNOVATION - Karekatt, Raphael (Asian Horizons, 2016)
Technology, envisioned and engineered by human innovative quest, has been an effective tool to humankind’s progress across the centuries. But when technology becomes so powerful as to usurp human decision making and the human person is so beholden to the spell of technology as to abdicate his/her role in making life’s choices and decisions, it does not bode well for humanity’s future. Technology appears to have staked a stranglehold on human affairs in the modern times, incapacitating the human person to decide for oneself, calling the very human identity itself. Modern medicine and health care is an area of modern life where this stranglehold of technology is most profoundly felt, determining every choice made on human health and wellness. The following reflection examines the current status of medicine being a hostage to technology and explores how to remedy the situation.